The Unique Context of Identity‐Based Student Organizations in Developing Leadership. Issue 155 (22nd August 2017) - Kodama, Corinne M.; Laylo, Rhonda
Abstract : This chapter addresses the important role of identity‐based student organizations in developing leadership, particularly for students who may feel marginalized because of their racial/ethnic, religious, or gender identities. Understanding the influence of these groups can help leadership educators develop a more inclusive and diverse perspective on student leadership development.